Technology for Arabic Learning as Foreign Language at Elementary School - Ritonga, Ahmad Roisuddin; Ritonga, Apri Wardana; Ritonga, Mahyudin; Desrani, Ayu (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
The implementation of face-to-face learning in the teaching of Arabic language in elementary schools is an effort to restore the quality of online learning. Therefore, this study aims to describe the management of face-to-face learning (FTF) implementation in Arabic language learning and the problems faced in elementary schools. The results showed that (a) the implementation of Arabic FTF in Elementary Schools has been carried out 100 percent with learning designs using "gamified" based media and contextual methods, such as snakes and ladders as well as the knowledge trees in the teaching of vocabulary, and (b) the problem of the implementation was derived from the learning process, such as ignoring health protocols, reducing the enthusiasm for FTF learning of students due to more than 2 years of online class. Other problems originated from parents who are not optimal in accompanying their children’s learning process at home. Furthermore, it was revealed that contextual learning media that are appropriate for students' age can make the learning process fun and enjoyable.